PREGNANCY IN EPILEPSY: AN EVIDENCE-BASED MEDICINE APPROACH - P. N. Vlasov (Эпилепсия и пароксизмальные состояния, 2016)
The article touches upon major issues related to pregnancy in epilepsy using the authors’ own experience and results of 3 latest studies carried out by American researchers and analyzed with an evidence-based medicine approach.